Analysis of The Relationship Between Polypharmacy and Potentially Inappropriate Medications (PIMs) Based on The 2023 Beers Criteria in Geriatric Diabetes Mellitus Patients - Oktavian Asyon Herlambang; Aprilia Puteri Santika; Septian Maulid Wicahyo (Universitas Duta Bangsa Surakarta, 2026)
Background: Diabetes mellitus can cause various complications if it is not controlled, resulting in the risk of increasing the number drugs prescribed. The number of medications is one factor that can describe the incidence of Potentially Inappropriate Medications (PIMs). Objectives: This Research is to determine the percentage of PIMs based on the Beers Criteria 2023 and to determine the relationship between the number of drug prescriptions and the incidence of PIMs. Methods: used is descriptive observational. A sample of 120 recipes was carried out using purposive sampling which met the inclusion criteria. Data analysis using the chi square test and correlative contingency coefficient test. Results: the research showed that the demographic characteristics of geriatric diabetes mellitus patients at RSU Asy Syifa' Sambi Boyolali for the period January-March 2025 were dominated by female patients of 76 patients (63.33%), the majority aged 60-69 years, namely 83 patients (69.17%), the number of drugs ? 5 namely of 78 patients (65%), and 114 patients (95%) had comorbidities.There is a percentage of PIMs in the amount of 32.24% of the total drug items, the highest number of PIMs is category 2, namely 32.49%. Based on the results of statistical tests, it shows a p-value of 0.217 (p > 0.05), which means there is no statistically significant relationship between the amount of medication and the incidence of PIMs. Apart from that, the correlation coefficient value for the two variables is 0.112, indicating that the level of strength of the relationship is in the very weak category. Conclusion: An increasing the number of prescribed medications is not the only factor contributing to PIMs. The association between polypharmacy and PIM was not statistically significant (p=0.217) and showed a very weak value. These findings emphasize that in geriatric diabetes care, quality prescribing, appropriate management of complex comorbidities, and regular clinical monitoring effectively reduce the risk of polypharmacy. Therefore, evaluating the appropriateness of therapy is far more important than simply limiting the number of medications.